Stop Contact Controlled By Android App Via Bluetooth - Benny Agus Simanungkalit (Journal of Science Technology (JoSTec), 2019)
Sockets are electrical equipment that has been used to connect and disconnect electricity from a power source to electrical equipment. Rapid technological developments encourage people to create a reliable and easy-to-operate socket. So far, the operation of the socket is done manually by pressing the socket. The very rapid development of technology has encouraged people to create electrical plugs with greater capabilities and ease of use. Therefore, designed an electrical plug that can be controlled by an android smartphone. For operation through the android application, sensors are needed that can be used to detect all the parameters needed in the use of sockets, there are several sensors used, namely current sensors, voltage sensors, and bluetooth. This sensor is connected to the Arduino UNO. By using the android application, we no longer need to walk to the location of the socket, simply by giving an order via android then the task of the socket can be carried out.